Pathogenic free-living amoebae in Korea - Shin, Ho-Joon (The Korean Society for Parasitology, 2004)
Acanthamoeba and Naegleria are widely distributed in fresh water, soil and dust throughout the world, and cause meningoencephalitis or keratoconjunctivitis in humans and other mammals. Korean isolates, namely, Naegleria sp. YM-1 and Acanthamoeba sp. YM-2, YM-3, YM-4, YM-5, YM-6 and YM-7, were collected from sewage, water puddles, a storage reservoir, the gills of a fresh water fish, and by corneal washing. These isolates were categorized into three groups based on the mortalities of infected mice namely, highly virulent (YM-4), moderately virulent (YM-2, YM-5 and YM-7) and nonpathogenic (YM-3). In addition, a new species of Acanthamoeba was isolated from a freshwater fish in Korea and tentatively named Korean isolate YM-4. The morphologic characters of its cysts were similar to those of A. culbertsoni and A. royreba, which were previously designated as Acanthamoeba group III. Based on experimentally infected mouse mortality, Acanthamoeba YM-4 was highly virulent. The isoenzymes profile of Acanthamoeba YM-4 was similar to that of A. royreba. Moreover, an anti-Acanthamoeba YM-4 monoclonal antibody reacted only with Acanthamoeba YM-4, and not with A. culbertsoni. Random amplified polymorphic DNA marker analysis and RFLP analysis of mitochondrial DNA and of a 18S small subunit ribosomal RNA, placed Acanthamoeba YM-4 in a separate cluster based on phylogenic distances. Thus Acanthamoeba YM-4 was identified as a new species, and assigned Acanthamoeba sohi. Up to the year 2002 in Korea, two clinical cases were found to be infected with Acanthamoeba spp. These patients died of meningoencephalitis. In addition, one case of Acanthamoeba pneumonia with an immunodeficient status was reported and Acanthamoeba was detected in several cases of chronic relapsing corneal ulcer, chronic conjunctivitis, and keratitis.